Implementing W2Share: Supporting Reproducibility and Quality Assessment in eScience - Carvalho, Lucas; Malaverri, Joana; Medeiros, Claudia (Anais do Brazilian e-Science Workshop (BreSci), 2017)
An open problem in scientific community is that of supporting reproducibility and quality assessment of scientific experiments. Solutions need to be able to help scientists to reproduce experimental procedures in a reliable manner and, at the same time, to provide mechanisms for documenting the experiments to enhance integrity and transparency. Moreover, solutions need to incorporate features that allow the assessment of procedures, data used and results of those experiments. In this context, we designed W2Share, a framework to meet these requirements. This paper introduces our first implementation of W2Share, which moreover guides scientists in step-by-step process to ensure reproducibility based on a script-to-workflow conversion strategy. W2Share also incorporates features that allow annotating experiments with quality information. We validate our prototype using a real-world scenario in Bioinformatics.